Sequence and molecular characterization of a DNA region encoding a small heat shock protein of Clostridium acetobutylicum. - Sauer, U (1993)
A DNA region of Clostridium acetobutylicum containing a gene (hsp 18) with significant homology to a family of small eukaryotic heat shock proteins was cloned and sequenced. It is the second reported sequence of a low-molecular-weight heat shock protein from gram-positive bacteria and is induced not only by heat shock but also at the onset of solventogenesis, as determined by Northern (RNA) blot analysis, thus confirming the results of an earlier study performed at the protein level (A. Pich, F. Narberhaus, and H. Bahl, Appl. Microbiol. Biotechnol. 33:697-704, 1990). By primer extension analysis, a transcriptional start site was identified 149 bp upstream of hsp18. This site was preceded by a region that exhibits high homology to the consensus promoter sequences of gram-positive bacteria, as well as sigma 70-dependent Escherichia coli. A direct repeat structure was detected in the -35 region. The promoter is located 196 bp from the start of a potential regulatory tRNA(Thr)ACG gene involved in the shift to solventogenesis which is transcribed in the opposite direction. A putative rho-independent transcription termination structure was identified at the 3' end of hsp18.